The Effect of Exclusive Breastfeeding on Illness Frequency of The Baby - Amalia, Rizki (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Exclusive breastfeeding is the most suitable nutrient for babies for 0-6 months. In reality, exclusive breastfeeding is still far from the expected target. Meanwhile, it was still found that many numbers of ill babies visit. This study aims to find out the illness frequency difference between the 2 year ill babies who got exclusive breastfeeding and babies who did not get exclusive breastfeeding. This research was a retrospective analytical study. The average number of illness frequency of 2 year ill babies was 5 times. After being analyzed, it was obtained that p = 0.030 Ho Ho was rejected and H1 was accepted. Bthat there is difference between the 2 year ill babies who got exclusive breastfeeding and babies who did not get exclusive breastfeeding. It means that exclusive breastfeeding can affect the illness frequency of baby. Therefore, it is recommended that breastfeeding mothers should give exclusive breastfeeding to their babies